Study Method of Dynamic Performance of Spiral Bevel Gear based on Abaqus - Gang Wei; Zhonghou Wang; Han Wu (Jixie chuandong, 2019)
Taking the 3D model of spiral bevel gear built by CATIA through the secondary development as research object， the simulation analysis of spiral bevel gear is carried out by using Abaqus software， and the dynamic performance of spiral bevel gear under different loads is simulated. The contact analysis s conducted and the curve of transmission error is extracted. The results show that the fluctuation amplitude of gear transmission error decreases with the increase of load， but the deviation from the zero line increases. It indicates that the spiral bevel gear drives more smoothly with increased load， the transmission accuracy decreased accordingly.